2014
DOI: 10.5901/mjss.2014.v5n16p239
|View full text |Cite
|
Sign up to set email alerts
|

The Religious Practices Teaching Pedagogy of Islamic Education Excellent Teachers

Abstract: An Islamic Education Excellent Teacher's (IEET) expertise can be assessed through his teaching techniques. An IEET usually possesses strong Pedagogical Content Knowledge. This study was carried out to investigate an IEET's interest and knowledge of pedagogical content in teaching Islamic Education Religious Practices subject. This study used a qualitative approach to the framework of the case study. The subject of the study is a DG 44 graded IEET with 10 years' experience in teaching Islamic Education. The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…In practice, teachers execute different methods and strategies anchored to different instructional models to perform efficient academic tasks (Trigwell & Prosser, 2004): for instance, how to effectively and efficiently translate competencies embedded in the curriculum during actual teaching, execute classroom management, and incorporate studentcentered approach to learning among others. In general, pedagogical practices of Madrasah teachers can be best understood when based on the different factors that influence their overall practices to include the following: self-efficacy (Abdullah, 2018;Alotaibi, 2014;Amri et al, 2017;Barni et al, 2019;Faizuddin, 2016;Hussin et al, 2014;Liu et al, 2018); educational background including Islamic education (Halstead, 2004;Hasyim, 2016;Memon, 2011;Sabki & Hardaker, 2013;2015;Tengku Kasim & Abdurajak, 2018); trainings and seminars attended during their pre-service or in-service (Alwadai, 2014;Sali & Marasigan, 2020); and even peer mentoring (Solaiman, 2017). Pedagogical praxis as a form of experience-based professional learning allows the teacher to improve their professional as well as personal competencies (Sirotová, 2016).…”
Section: On the Pedagogical Praxis Of Madrasah Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, teachers execute different methods and strategies anchored to different instructional models to perform efficient academic tasks (Trigwell & Prosser, 2004): for instance, how to effectively and efficiently translate competencies embedded in the curriculum during actual teaching, execute classroom management, and incorporate studentcentered approach to learning among others. In general, pedagogical practices of Madrasah teachers can be best understood when based on the different factors that influence their overall practices to include the following: self-efficacy (Abdullah, 2018;Alotaibi, 2014;Amri et al, 2017;Barni et al, 2019;Faizuddin, 2016;Hussin et al, 2014;Liu et al, 2018); educational background including Islamic education (Halstead, 2004;Hasyim, 2016;Memon, 2011;Sabki & Hardaker, 2013;2015;Tengku Kasim & Abdurajak, 2018); trainings and seminars attended during their pre-service or in-service (Alwadai, 2014;Sali & Marasigan, 2020); and even peer mentoring (Solaiman, 2017). Pedagogical praxis as a form of experience-based professional learning allows the teacher to improve their professional as well as personal competencies (Sirotová, 2016).…”
Section: On the Pedagogical Praxis Of Madrasah Teachersmentioning
confidence: 99%
“…According to Hussin et al (2014), there were three significant themes identified on teaching practices of Islamic teachers: material-resource centered; teacher-centered; and studentcentered teaching method of religious subject. Similar to the results of Hussin et al (2014), the Asatidz understood the importance of well-organized pedagogical practices in guiding the students to learn. Most of these participants preferred well-initiated collaborative classroom activities and teaching methodologies.…”
Section: Collaborative Learning Practicesmentioning
confidence: 99%
“…In practice, teachers execute different methods and strategies anchored to different instructional models to perform efficient academic tasks (Trigwell & Prosser, 2004): for instance, how to effectively and efficiently translate competencies embedded in the curriculum during actual teaching, execute classroom management, and incorporate studentcentered approach to learning among others. In general, pedagogical practices of Madrasah teachers can be best understood when based on the different factors that influence their overall practices to include the following: self-efficacy (Abdullah, 2018;Alotaibi, 2014;Amri et al, 2017;Barni et al, 2019;Faizuddin, 2016;Hussin et al, 2014;Liu et al, 2018); educational background including Islamic education (Halstead, 2004;Hasyim, 2016;Memon, 2011;Sabki & Hardaker, 2013;Tengku Kasim & Abdurajak, 2018); trainings and seminars attended during their pre-service or in-service (Alwadai, 2014;Sali & Marasigan, 2020); and even peer mentoring (Solaiman, 2017). Pedagogical praxis as a form of experience-based professional learning allows the teacher to improve their professional as well as personal competencies (Sirotová, 2016).…”
Section: On the Pedagogical Praxis Of Madrasah Teachersmentioning
confidence: 99%
“…Lastly, Hussin et al (2014) have shown that diversification of pedagogical approaches identifies three significant themes regarding the teaching practices of Islamic teachers: a material-resource centered theme; a teacher-centered theme; and a student-centered teaching method of religious subject. Significantly, Islamic teachers' well-organized pedagogical practices spell difference in guiding the students' learning.…”
Section: On the Pedagogical Praxis Of Madrasah Teachersmentioning
confidence: 99%
“…Facing the life of Melinia, Islamic religious education is present as a counterweight to the order of life of a person to manage reason, mind and ethics, Islam is not only studied as a theory in the classroom, but rather the practice of good behavior in everyday life, understanding and practicing the contents of the teachings of Islam well is a manifestation of one's belief in God Almighty and can build the power of emotional enthusiasm and indirectly form a character [1][2][3].…”
Section: Introductionmentioning
confidence: 99%